CITIZENSHIP EDUCATION (CIVIC EDUCATION) IN THE ERA OF DEMOCRATIZATION - Ramadhona, Agustian (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
This paper discusses about the linkage of democracy and civic education. Civic education is a vehicle to sustain and develop democracy. It is important to create democratic citizens and to support democracy. In response to the process of democracy in Indonesia, civic education should be reformed in order to prepare students to be good citizens. Effective civic education for democratic citizenship treats three basic components; knowledge of citizenship and government in democracy, cognitive skills of democratic citizenship, disposition and development characteristics of democratic citizenship